Changes in tissue oxygen saturation with well- and tight-fitted compression sleeves during an incremental Exercise on Treadmill - Peseux, M.; Muzic, J.; Bouhaddi, M.; Menetrier, A. (Asian Journal of Sports Medicine, 2017)
Background: Effects of lower-limb compression garments on hemodynamics during walking or running remain unclear.